Implementasi Sistem Manajemen Mutu Iso 9001:2000 Di Perpustakaan - Aziz, Syafrudin (STAIN Ponorogo, 2011)
This writing will be discussing about quality standardmanagement implementation system of ISO 9001:2000 in libraryinstitution. The word ISO is taken from greek which meansâsameâ and 9001 is a standard related to quality management. Theimplementation of ISO in library is a sustainable process whichneeds all supports. To apply it, needs fourth steps; 1) planning. 2)document compiling and validating. 3) certification. The advantagesof the implementation of ISO are: first, promoting the trust andlibrary user satisfactory by means of organized and systematicquality insurance. Second, promoting, image and competitivestrength in the global market. Third, promoting the awareness oflibrary quality. Fourth, triggering and creating positive changes interms of quality culture at the institution of library.